The ACTIVE Cognitive Training Interventions and Trajectories of Performance Among Older Adults. (December 2013) - Jones, Richard N.; Marsiske, Michael; Ball, Karlene; Rebok, George; Willis, Sherry L.; Morris, John N.; Tennstedt, Sharon L.
Objectives: Salthouse illustrated that among Advanced Cognitive Training for Independent and Vital Elderly (ACTIVE) participants, cognitive change accelerated following training. Our goal was to determine if this finding persists net of practice, training, and loss of training gains effects.Methods: We evaluated change over 5 years following cognitive training among older adults ( N = 1, 659, age 65 to 94).Results: Reasoning training, but not memory or speed, attenuated aging-related change. Memory gains were maintained, but about half of reasoning and speed gains were lost. Performance differences at the end of the follow-up were equivalent to about 6, 4, and 8 years of aging for memory, reasoning, and speed training, respectively.Discussion: Training can appear to accelerate age-related change, because change over time is coupled with loss of training gains. Our analysis is limited by follow-up that is short for precisely characterizing aging-related change.